The Future of Sustainability - Keiner, Marco (Springer Netherlands : Imprint: Springer, 2006)
At the beginning of the 21st Millennium, outstanding visionary thinkers and scientists make a timely assessment as to the future prospects of mankind: In what direction are we heading? How can the world become more just and equitable, and how can future development be sustained to adequately address economic, social, and -perhaps most important- environmental issues? This book provides a broad discussion on Sustainable Development, rethinking and improving its effectiveness as a paradigm of today and tomorrow by bringing together the visions and contributions of highly esteemed thinkers on the subject (such as Herman E. Daly, Ernst Ulrich von Weizsäcker, Mikhail Gorbachev, Dennis Meadows and others). Communities, states, and transnational corporations must take steps to transform engrained practices and priorities. If they fail to do so, Sustainable Development will remain an abstract concept or a superficial catchword and will not become reality. This publication is of special interest for university researchers and students, international experts and organizations in the field of Sustainable Development, but also for decision-makers of enterprises and the public sector worldwide. From each Author's thoughts, experiences and concerns the reader will learn about what the concept of Sustainable Development can really accomplish and where future needs for action are.